Web Writing - Pfannenstiel, Amber Nicole (Open textbook library., 2023)
Web Writing (2023) by Dr. A Nicole Pfannenstiel is designed to provide a practical, rhetorical approach to web writing and content strategy analysis for students completing advanced writing courses. The eTextbook uses the rhetorical situation and key concepts to help readers/students understand how to write within specific web spaces for specific audiences drawing on appropriate discourse community conventions. It includes a chapter devoted to the rhetorical situation and key concepts to help students analyze and build their understanding of existing communication. It also includes a chapter outlining approaches to content strategy analysis, using the rhetorical situation and key concepts to understand the rich public data provided through social media accounts to support learners understanding effective web writing. The content analysis overview helps students build skills for analyzing writing, for collecting and analyzing qualitative and quantitative social media data, and for drawing conclusions about content strategy best practices.